(untitled) (Swiss Medical Weekly, 2025)
INTRODUCTION: Long-term survival in lung transplant recipients is limited by chronic lung allograft dysfunction, which can be triggered by respiratory tract infections. STUDY AIMS: We investigated the incidence of chronic lung allograft dysfunction in a cohort of lung transplant recipients over 10 years, focusing on its association with human coronavirus (HCoV) respiratory tract infections and all-cause mortality. METHODS: This 10-year retrospective cohort included 259 lung transplant recipients between 2010 and 2020. Nasopharyngeal swab samples were analysed during regular outpatient visits and when symptoms indicated respiratory tract infections using a multiplex polymerase chain reaction panel to test for HCoV subtypes 229E, HKU1, NL63, and OC43. Data regarding chronic lung allograft dysfunction, clinical characteristics, infectious parameters, and lung function tests were recorded. An adjusted Cox proportional hazards regression model was applied. RESULTS: 166 lung transplant recipients survived the early postoperative period. Over a cumulative observation period of 711.4 patient-years, 57.8% (96/166) of patients were confirmed to have had at least one HCoV infection. On average, the incidence of HCoV respiratory tract infections (n = 380) was 0.53±0.33 per patient-year, and 32.9% (125/380) of respiratory tract infections were in asymptomatic patients. In routine follow-up visits, patients were tested for HCoV infections based on unclear inflammatory responses. Chronic lung allograft dysfunction developed in 45.8% (76/166) of lung transplant recipients. HCoV infections were associated with a higher subsequent likelihood of chronic lung allograft dysfunction (hazard ratio [HR] adjusted = 2.52, 95% CI 1.32–4.80, p = 0.005). After contracting HCoV infections, lung transplant recipients experienced higher C-reactive protein levels on days 4 and 5 after the infection, but there were no immediate changes in lung function parameters. CONCLUSION: While HCoV infections may not always show symptoms, they may increase the likelihood of subsequent chronic lung allograft dysfunction in lung transplant recipients.